The Potential of a Water-in-Diesel Emulsion for Increased Engine Performance and as an Environmentally Friendly Fuel - Nour, A. H.; R. M., Yunus; Azhari, H. Nour; Abdul Adam, Abdullah (EDP Sciences, 2016)
With increasing energy prices and the drive to reduce CO2 emissions, universities and industries face the challenge of finding new technologies to reduce energy consumption, to meet legal emission requirements and to reduce cost while increasing quality. In this study, an experiment was conducted to investigate the effect of water-in-diesel (WiDE) emulsions on the combustion performance and emulsion characteristics of a direct injection diesel engine under 0 to 50% engine loads at 0 to 300 psi with engine operating speeds of 1200 to 2500 rpm. The five types of emulsified diesel fuel used in this study consisted of WiDE-5%, WiDE-10%, WiDE-20%, WiDE-30% and WiDE-40% with 3% of the surfactants tested. The results show that 15-85% emulsion diesel fuel is comparable and compatible with pure diesel. The power curve shows the emulsion diesel to be relatively similar to pure diesel, but with slightly higher results at 0% (0 psi). The torque curve at 0% also shows the emulsion diesel to be similar to pure diesel where the 15 - 85% torque is higher than that of pure diesel. The engine torque, power and brake efficiency increase as the water percentage in the emulsion increases. The NO and CO2 emission results of the 15-85% fuel were better than that of pure diesel; however, the CO emissions were higher, especially at higher engine speeds.